2022
DOI: 10.1111/acps.13412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high frequency versus theta‐burst repetitive transcranial magnetic stimulation on suicidality in patients with treatment‐resistant depression

Abstract: Objective: To investigate the effect of 10 Hz repetitive transcranial magnetic stimulation (rTMS) and intermittent theta-burst stimulation (iTBS) on suicidality in patients with treatment-resistant depression (TRD). Methods:We used data from a three-site randomized clinical trial comparing 10 Hz rTMS and iTBS applied to the left dorsolateral prefrontal cortex (DLPFC) in patients with TRD. We compared the effect of 10Hz rTMS and iTBS on suicidality as measured by the suicide item of the Hamilton Depression Rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Following the implementation of repetitive TMS, the cognitive function score of study group was higher than control, indicating that the combined therapy improved cognitive function, possibly because TMS can excite or inhibit the cerebral cortex function through the application of different frequencies, thus exerting a two-way regulatory function in the brain. The use of repetitive TMS has also been shown to significantly improve cognitive function through intensive treatment of different regions of the brain, in a manner dependent on treatment intensity, frequency, and coil direction[ 20 ]. Our study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Following the implementation of repetitive TMS, the cognitive function score of study group was higher than control, indicating that the combined therapy improved cognitive function, possibly because TMS can excite or inhibit the cerebral cortex function through the application of different frequencies, thus exerting a two-way regulatory function in the brain. The use of repetitive TMS has also been shown to significantly improve cognitive function through intensive treatment of different regions of the brain, in a manner dependent on treatment intensity, frequency, and coil direction[ 20 ]. Our study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The most prolific author is Daskalakis, Zafiris J from the University of Toronto, Canada, with an average of 11.8 publications per year. His main research interests are clinical trial studies of various forms of TMS and different treatment sites and frequencies for depression[20][21][22][23][24]. Through the author co-occurrence visualization mapping we found that most of the authors have some collaborative relationships with each other, interlocking to form a network of relationships.…”
mentioning
confidence: 96%